Yeni Medyada İllüstrasyon Ve Fotografik İnvazyon : Lucas Levitan - Atabek, Aslıhan (The Turkish Online Journal of Design Art and Communication, 2016)
With transformation process from classical or mass media to new media, similar movements like graffiti, which was firstly occurred as a social reaction and became an art branch, have been seen in the digital media. A movement in digital media has started by Lucas Levitan by illustrating on digital images similar to graffiti based on wall painting in the real media. In these movement called by Levitan as photographic invasion, pictures in digital media having copyrights are subjected to invasion, and pictures are deformed. The work which has been started by Levitan as instagram project is a good sample for examining illustration and manipulation issues in new media. For this reason illustration concept was examined in perspective of Levitan and photographic invasion. According to results of the study, photographic invasion is similar with graffiti which is a branch of art occurred a reaction of art to the right of property. In photographic invasion, illustrations on pictures without any permission for copyright, whereas in the graffiti compositions are installed on other’s right of property without permission. In this respect, photographic invasion is a candidate for literature, and the first argument of this was given in this research.
Keywords: Yeni medya; illüstrasyon; Lucas Levitan; fotografik invazyon; New media; illustration; Lucas Levitan; photographic invasion